Improving Cytomegalovirus-Specific T Cell Reconstitution after Haploidentical Stem Cell Transplantation - Xiao-Hua Luo; Ying-Jun Chang; Xiao-Jun Huang (Journal of Immunology Research)
Cytomegalovirus (CMV) infection and delayed immune reconstitution (IR) remain serious obstacles for successful haploidentical stem cell transplantation (haplo-SCT). CMV-specific IR varied according to whether patients received manipulated/unmanipulated grafts or myeloablative/reduced intensity conditioning. CMV infection commonly occurs following impaired IR of T cell and its subsets. Here, we discuss the factors that influence IR based on currently available evidence. Adoptive transfer of donor T cells to improve CMV-specific IR is discussed. One should choose grafts from CMV-positive donors for transplant into CMV-positive recipients (D+/R+) because this will result in better IR than would grafts from CMV-negative donors (D−/R+). Stem cell source and donor age are other important factors. Posttransplant complications, including graft-versus-host disease and CMV infection, as well as their associated treatments, should also be considered. The effects of varying degrees of HLA disparity and conditioning regimens are more controversial. As many of these factors and strategies are considered in the setting of haplo-SCT, it is anticipated that haplo-SCT will continue to advance, further expanding our understanding of IR and CMV infection.